2015
DOI: 10.1002/mrc.4371
|View full text |Cite
|
Sign up to set email alerts
|

13C‐TmDOTA as versatile thermometer compound for solid‐state NMR of hydrated lipid bilayer membranes

Abstract: Recent advances in solid-state nuclear magnetic resonance (NMR) techniques, such as magic angle spinning and high-power decoupling, have dramatically increased the sensitivity and resolution of NMR. However, these NMR techniques generate extra heat, causing a temperature difference between the sample in the rotor and the variable temperature gas. This extra heating is a particularly crucial problem for hydrated lipid membrane samples. Thus, to develop an NMR thermometer that is suitable for hydrated lipid samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Next, we examined the applicability of the 2 H chemical-shift thermometer ErDOTA-d 8 to the determination of the phase transition temperature of hydrated lipid bilayers. In our previous study on a 13 chemical-shift thermometer, [32] the thermometer compound was premixed with liposomes for solid-state NMR measurements because 13 C NMR measurements were largely performed under high-speed MAS conditions. Such conditions require well-balanced packing of the sample and high-power 1 H decoupling irradiation, which causes considerable inhomogeneity in temperature distribution.…”
Section: Temperature-dependent 2 H Chemical-shift Changes Of Lndota-dmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we examined the applicability of the 2 H chemical-shift thermometer ErDOTA-d 8 to the determination of the phase transition temperature of hydrated lipid bilayers. In our previous study on a 13 chemical-shift thermometer, [32] the thermometer compound was premixed with liposomes for solid-state NMR measurements because 13 C NMR measurements were largely performed under high-speed MAS conditions. Such conditions require well-balanced packing of the sample and high-power 1 H decoupling irradiation, which causes considerable inhomogeneity in temperature distribution.…”
Section: Temperature-dependent 2 H Chemical-shift Changes Of Lndota-dmentioning
confidence: 99%
“…[29][30][31] Recently, we reported that the 13 C chemical shift of the lanthanide Tm complex with 1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid (DOTA is a non-deuterated form of 4 in Scheme 1), TmDOTA, is highly temperature dependent and serves as a chemical-shift thermometer for 13 C solid-state NMR measurements of lipid bilayers. [32] Thus, we postulated that the 2 H-labeled lanthanide-DOTA complex, LnDOTA, could be a candidate for a 2 H chemical-shift thermometer. In this study, we prepared a series of 2 H-labeled LnDOTAs and investigated their temperature-dependent chemicalshift changes.…”
mentioning
confidence: 99%
“…[20d,21] In addition to 19 F, other hetero nuclei are also of interest. Recent results showed very high sensitives for 31 P [22] and 59 Co (up to 150 ppm/ K), [23] but nuclei such as 13 C [24] and 2 H [25] are also of interest.…”
Section: Introductionmentioning
confidence: 99%
“…One method for temperature detection via NMR utilizes a temperature-dependent chemical shift. This technique can use protons ( 1 H), 5-7 19 F, 8,9 13 C, 10,11 and 31 P. 12,13 Yet, the temperature sensitivities of these systems are often low, <1 ppm °C−1 (e.g, 0.01 ppm °C−1 for 1 H in H 2 O, 6 or 0.012 ppm °C−1 in 19 F as perfluorotributylamine 9 ). A related technique, PARACEST (PARAmagnetic Chemical Exchange Saturation Transfer), can imbue a temperature dependence to the 1 H chemical shift of bulk water through hyperfine coupling in open-shell lantha-nide complexes.…”
Section: Introductionmentioning
confidence: 99%